Structural modulation of gut microbiota during alleviation of non-alcoholic fatty liver disease with Gynostemma pentaphyllum in rats - Shu-Hua Shen; Ting-Yan Zhong; Cui Peng; Jie Fang; Bin Lv (BMC Complementary Medicine and Therapies, 2020)
Abstract Background The current work aimed to assess whether Gynostemma pentaphyllum (GP), a Chinese herbal medicine, structurally modifies the gut microbiota in rats during non-alcoholic fatty liver disease (NAFLD) treatment. Methods High-fat diet (HFD)-induced NAFLD rats were orally administered water decoction of GP or equal amounts of distilled water per day for 4 weeks. Liver tissues were examined by histopathological observation, while intestinal tissues were examined by both histopathological and ultrastructural observations. The levels of fasting blood glucose (FBG), fasting serum insulin (FINS), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), alanine transaminase (ALT) and aspartate transaminase (AST) were measured by enzymatic method. The levels of toll-like receptor 4 (TLR-4), tumor necrosis factor-alpha (TNF-α), interleukin-1-beta (IL-1β) and interleukin-6 (IL-6) in both serum and hepatic tissues were measured by RT-qPCR. The protein expression level of TLR-4 in hepatic tissues was detected by western blot. The gut microbiota was assessed by 16S rRNA-based microbiota analysis. Results GP maintained intestinal integrity and reversed gut dysbiosis in high-fat diet (HFD)-induced NAFLD rats. This also reduced the ratio of Firmicutes to Bacteroidetes, enriching the abundance of beneficial bacteria (Lactococcus spp.) and inhibiting the abundance of pathogenic bacteria (Ruminococcus spp.) in the gut. The levels of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6) and the expression of TLR4 were downregulated (P < 0.05), while the insulin resistance index, HOMA-IR showed improvement by GP treatment (P < 0.05). Liver function indicators (ALT and AST) were remarkably decreased (P < 0.01). Besides, GP treatment reduced TG and LDL-C levels (P < 0.05), and increased HDL-C level (P < 0.05) compared with NAFLD group. Conclusion The structural alterations of gut microbiota induced by GP are associated with NAFLD alleviation.